Explore carbon sink of bamboo with M+ living lab at Qingshan - Zhen, Yan; Yang, Xiaoneng; Chen, Kevin Z. (CGIAR System Organization, 2025)
This report explores how bamboo can function as a village-scale carbon sink and a catalyst for low-carbon transition, using Qingshan Village’s M+ Living Lab as a real-world test bed. First, it offers a concise review of research and practice on bamboo carbon sinks, summarizing scientific evidence on the high growth rate, biomass accumulation and soil carbon storage of Moso bamboo, as well as recent advances in accounting methods that range from traditional plot surveys to standardized project methodologies and remote-sensing–based, data-driven monitoring. It then examines the integration of bamboo into China’s carbon markets and broader climate policy framework, and highlights regional practices such as Anji’s bamboo carbon trading and loan schemes as examples of “bamboo-as-development-tool” linking carbon sinks, green finance and rural revitalization. The report also draws on work on exhibition spaces and Living Labs to show how bamboo carbon can be communicated and cocreated in everyday settings. Base on this review, the second part positions bamboo carbon sinks as one “piece of the puzzle” in Qingshan’s zero-carbon vision, rather than as a standalone project. It outlines a technical pathway from plot-level monitoring to a “zero-carbon digital brain” and village carbon ledger, and proposes embedding bamboo carbon information into local spaces, activities and governance processes. Finally, it identifies three innovation directions—multi-scale coupling, multi-stakeholder co-creation and a shift from “carbon sink project” to “way of life”—as the core contributions of the Qingshan M+ Living Lab exploration.